Effect of estrogen depression on alveolar bone microarchitecture and periodontal ligament cells during orthodontic movement - Ruivo, Andréa Karina; Calsa, Bruno; Cancellara, Matheus Gomez [UNESP]; Lima, João Paulo Nascimento; da Silva, Karla Rovaris; Esquisatto, Marcelo Augusto Marretto; Santamaria-Jr, Milton [UNESP] (Wiley, 2024)
This study aimed to evaluate the effects of the estrogen depression during orthodontic tooth movement on alveolar bone microarchitecture and periodontal ligament. Female Wistar rats were divided into two groups, one consisting of non-ovariectomized animals subjected to orthodontic tooth movement, and one comprising ovariectomized animals subjected to orthodontic tooth movement. Micro-CT assessment of bone volume to total volume (BV/TV), total porosity, trabecular thickness (Tb.Th), trabecular number (Tb.N), and trabecular separation (Tb.Sp) in the alveolar bone of the orthodontically moved tooth was performed. Histomorphometric analyses were made in the periodontal ligament, and immunoexpression of RANK, RANKL, OPG, and TUNEL were quantified. Orthodontic tooth movement in the group of ovariectomized rats was faster than in non-ovariectomized animals. The alveolar bone area showed lower values of BV/TV and trabecular thickness, and higher bone porosity and trabeculae numbers in the ovariectomized rats. Histological analyses in the ovariectomized group revealed an increase in collagen fibers in the periodontal ligament. The apoptotic cell counts in the periodontal ligament were higher in the group of ovariectomized rats than in the sham-operated rats. Ovariectomy resulted in an increase in tooth movement and alteration of the alveolar bone microstructure in the first 7 day of orthodontic tooth movement, and in the presence of apoptotic cells in the periodontal ligament.
Keywords: apoptosis; collagen fibers; estrogen; micro-CT; orthodontic tooth movement